On-site treatment of hospital wastewater in a full-scale treatment plant in Germany: SARS-CoV-2 and treatment performance. (24th March 2023) - Haeusser, Sarah; Weber, Martin; Mauer, Christian; Linnemann, Volker; Pfannstiel, Anna; Pinnekamp, Johannes; Wintgens, Thomas; Klümper, Claudia; Beier, Silvio
Abstract: The separate, advanced treatment of hospital wastewater might be a promising approach to prevent the dissemination of residual compounds of high environmental concern, like pharmaceuticals, viruses and pathogenic microorganisms. This study investigates the performance of a full-scale, on-site treatment plant, consisting of a membrane bioreactor and a subsequent ozonation, at a German hospital. We analysed the elimination of pharmaceutical residues, microbiological parameters and SARS-CoV-2 RNA fragments. Additionally, we conducted an orienting study on the practicability of implementing targeted wastewater monitoring at a hospital. Our results demonstrate that after 10 years of stable operation, the treatment plant works highly efficiently regarding the elimination of pharmaceuticals and bacterial indicators. Elimination rates for pharmaceutical substances were above 90%, and log reductions of up to 6 log10 units for microbiological parameters were achieved. SARS-CoV-2 RNA could be detected and quantified in the influent but not in the effluent. The RNA load in the raw wastewater showed good correspondence with COVID-19 case numbers in the hospital. We showed that the full-scale on-site treatment of hospital wastewater is technically feasible and contributes to sustainable hospital effluent management and that monitoring biological markers on the building level might be a useful complementary tool for disease surveillance. HIGHLIGHTS: Separate on-site treatment of hospital wastewater with a membrane bioreactor and subsequent ozonation is a promising treatment technology to cope with future challenges in wastewater management like micropollutants and microbial hazards. Elimination rates of over 90% for pharmaceutical residues and removals of up to 6 log10 units for bacterial indicators were achieved by a full-scale hospital wastewater treatment plant (WWTP). Graphical Abstract